THE IMPORTANCE OF HEALTH EDUCATION REDUCE STRESS LEVEL IN CATARACS OPERATION CLIENTS IN MANADO EYE HOSPITAL UPTD - Ferdinand Gansalangi; Kezya Rumengan; Jon W. Tangka; Janbonsel Bobaya (POLITEKNIK KESEHATAN KEMENTERIAN KESEHATAN MANADO, 2019)
Introduction: Cataracts occur as a result of the opacification of the lens of the eye which decreases vision ability until blindness. The risk of blindness caused by cataracts can be cured through surgical removal of cataracts. Cataract surgery is a stressor for patients with cataracts. One of the measures to reduce stress levels before surgery is to prepare the patient's mentality. Mental preparation of patients can be done through Health Education. Health education in preoperative patients is provided with the aim of providing information relating to preoperative preparation. Purpose: The purpose of this study is to determine whether there is an influence of health education on stress levels in pre-cataract surgery clients at UPTD Manado Eye Hospital. Method: The design of this study used a quasi-one-group pre-post-test test and accidental sampling technique of 30 respondents and data analysis using the Wilcoxon Signed Rank Test. Results : The results of the study showed that there was a significant influence on health education on stress levels in pre-cataract surgery clients with a p-value of 0,000, meaning that the P-value α ≤ 0.05. Discussion: According to researchers, health education plays an important role in reducing stress levels in someone who will undergo cataract surgery. By providing preoperative health education the client will obtain clear information about the illness and the operating experience that will be faced so as to reduce the level of stress on the preoperative client. Referring to the opinion of Induniasih and Ratih (2017), that health education is all efforts to educate, provide information, knowledge, skills to improve the quality of health, both at the individual, group, and community level. Conclusion: The conclusion of this study is that health education can reduce the level of stress a person faces in cataract surgery. Suggestions for further researchers can do research with different methods or types of research or conduct research on the same topic with different samples that can represent the population, so they can compare the results of research.